THE IMPLEMENTATION OF ONLINE LEARNING IN ENGLISH LANGUAGE TEACHING DURING PANDEMIC: THE TEACHERS VOICE - Mutiara Ayu; Zakiyah Farhanah Pratiwi (Universitas Teknokrat Indonesia, 2021)
This study aims to explore the implementation of website that used in MAN 2 Bandarlampung. To overcome the problem structurally, the theoretical framework by discussing about theory and approach was conducted. The theories applied helped in finding out the implementation of this website. Meanwhile the approach was emphasized on one approach that is online media learning in the learning process during pandemic. Moreover, this analysis applied descriptive qualitative method to depict clearly about the problem by using the words. The result of this analysis shows that the use of online learning, especially Rumah Belajar brings some factors for the teachers in deliver the material. First factor is from the technology, it has some benefits and also problems for the teacher. The second factor is the teachers behavior in using this website. It can be concluded this website is quite good to help the teacher to do the learning process during pandemic because this website has covered the teachers need, but the school has not explained some features, so it hinders the teacher from doing their best. The implementation of Rumah Belajar during pandemic must have sufficient training to help teachers do their teaching during e-learning maximally. As a result Rumah Belajar during pandemic can assist in the implementation of online learning.